A Study on The Completeness, Finite Verb Tense, and Voice of Coconut Research Abstracts - muhartoyo muhartoyo (Lingua Cultura, 2016)
Abstract is a secondary source of scientific information which can help scientists to get the gist of relevant information needed for their study. Scientific article usually provides informative abstracts to facilitate readers to know the essential content of the article. The quality of an abstract depends on the accuracy and completeness of abstract components or elements. This research was intended to find out the completeness of abstract elements, finite verb tenses, and the voice of coconut research abstracts. A total of 34 abstracts from the last three-year issues of CORD journal were analyzed. The result of the analysis showed that there were two categories i.e. indicative abstracts (21%) and comprehensives abstracts (79%). The most complete informative abstracts consisting of 5 elements accounted for 23%, the informative abstracts with four elements had the highest amount which was 41%, and the informative/comprehensive abstracts with three elements had the least amount which is 15%. It can be concluded that most informative/ comprehensive abstracts contain four elements which are background (introduction), objectives, methodology, and result. Four tenses are usually used in abstract writing; they are simple present, simple past, present and past perfect tense. Both active and passive voices are used in writing abstracts.